Recombinant Lactococcus Lactis Expressing M1-HA2 Fusion Protein Provides Protective Mucosal Immunity Against H9N2 Avian Influenza Virus in Chickens - Sha, Zhou; Shang, Hongqi; Miao, Yongqiang; Huang, Jin; Niu, Xiangyun; Chen, Ruichang; Hu, Liping; Huang, He; Wei, Kai; Zhu, Ruiliang (Frontiers in Veterinary Science, 2020)
Abstract: The H9N2 subtype of the low pathogenic avian influenza virus (LPAIV) is distributed worldwide and causes enormous economic losses to the poultry industry. In this study, Lactobacillus expressing the H9N2 virus M1-HA2 fusion protein was used to investigate the impact on the protection effectiveness and mucosal immunity in chickens. Chickens orally vaccinated with NZ9000/pNZ8148-M1-HA2 showed significant increase in the levels of hemagglutination inhibition (HI) antibodies, T cell-mediated immune responses, and mucosal secretory IgA (SIgA). Following H9N2 challenge, weight loss, lung virus titer, and lung pathology were improved. Our results indicate that the recombinant Lactobacillus can improve the intestinal immune function and provide effective protection in chicken. This trial provides a theory for the development of microecological preparations for the prevention of H9N2 avian influenza.